Cover Picture: Hepatocyte‐Specific Delivery of siRNAs Conjugated to Novel Non‐nucleosidic Trivalent N‐Acetylgalactosamine Elicits Robust Gene Silencing in Vivo (ChemBioChem 6/2015). Issue 6 (13th April 2015) - Rajeev, Kallanthottathil G.; Nair, Jayaprakash K.; Jayaraman, Muthusamy; Charisse, Klaus; Taneja, Nate; O'Shea, Jonathan; Willoughby, Jennifer L. S.; Yucius, Kristina; Nguyen, Tuyen; Shulga‐Morskaya, Svetlana; Milstein, Stuart; Liebow, Abigail; et al.
<x xml:space="preserve">Abstract</x> The cover picture shows recognition of siRNA conjugated to trivalent N‐acetylgalactosamine by the asialoglycoprotein receptor (ASGPR) expressed on the surface of a hepatocyte, and intracellular events that result in gene silencing. In nature, ASGPR mediates clearance of "dead" glycoproteins from circulation. This natural molecular machinery, which recognizes exposed galactoses, has been exploited to deliver nucleic acid‐based drugs into hepatocytes. Engineered GalNAc moieties in favorable proximity and optimal spatial orientation serve as ligand mimics and are recognized by ASGPR leading to cargo internalization. GalNAc monomers were synthesized by using non‐nucleosidic tethers and incorporated via phosphodiester linkages into oligonucleotides. The optimal siRNA‐GalNAc conjugate was prepared by sequential covalent incorporation of three single GalNAc moieties at the 3′‐end of the sense strand of siRNA. The siRNA–GalNAc conjugate elicited robust gene silencing in liver. Clinical experience with siRNA–GalNAc indicates that this strategy is a breakthrough in the tissue‐specific delivery of therapeutic nucleic acids. For more details see the communication by K. G. Rajeev, M. Manoharan et al. on p. 903 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>